Strategi Kepemimpinan Kepala Sekolah Dalam Meningkatkan Kinerja Guru - Nofi Lalomo; Syahril Muhammad; Abdullah W. Jabid (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The purpose of this study was to determine the principal's leadership strategy in improving teacher performance. This type of research uses qualitative research methods. Data were collected through observation, in-depth interviews and documentation. The results of this study show that the principal's leadership strategy in improving the performance of teachers of SD Naskat Golo, Sahu District, West Halmahera Regency by increasing teacher work discipline, providing motivation, being an example by providing the best example in all actions at school, and supervising, among others, supervising, assessing and evaluating the performance of teachers and education staff. In overcoming obstacles in the process of improving teacher performance at SD Naskat Golo, Sahu District, West Halmahera Regency, namely improving the realm of discipline by giving warnings and reprimands, providing motivation in developing human resources, conducting supervision once a quarter by involving supervisors